Logistics & supply chain management - Christopher, Martin
Effective development and management of supply chain networks helps businesses cut costs and enhance customer value. This 5th edition provides the most up-to-date practical tools to manage the people and processes that allow businesses to gain and maintain competitive advantage through their supply chains